Cultural centres as an element of socialist modernization of village areas in Lithuania - Petrulis, Vaidas (Journal of Architecture and Urbanism, 2012)
The article analyses the building boom of Houses of Culture in Lithuanian SSR during the time of socialist modernism. The object of the paper is being analyzed with an attempt to reveal the tight relation between political, economic and architectural spheres. First of all research concentrates on questions of Soviet ideological and economic interests and the result of these interests –a regional planning scheme of Lithuania, which has been implemented through the principles of modernism, and especially Constantine’s Doxiadis idea of “total architecture”. Then the text analyses how these principles of mid-century modernism have been transferred through the prism of ideology and, in Lithuanian case, led to very painful social consequences - massive displacing of individual home-steads and transferring the inhabitants to the newly created settlements. The House of Culture is presented as the representative face of these political-economic objectives of rural modernization. The article also makes a suggestionthat these objects are an interesting and important part of modernist legacy of Lithuania, perfectly reflecting interconnections between international modernism and the ideology of the Soviets under the circumstances of local provincial life. Article in Lithuanian. Kultūros namai kaip socialistinės Lietuvos kaimo modernizacijos elementas Santrauka. Straipsnyje analizuojamas buvusios Lietuvos SSR kultūros namų statybos bumas socialistinio modernizmo laikotarpiu. Darbo objektas tekste tiriamas siekiant atskleisti glaudžią politinių, ekonominių bei architektūrinių veiksnių sąveiką. Tekste nagrinėjama, kaip veikiant ideologiniams bei ekonominiams interesams formuojamas urbanistinis Lietuvos tinklas, kuris buvo įgyvendinamas pasinaudojant modernizmo ir ypač Konstantino Doksiadžio „totalinės architektūros“ idėjomis. Toliau pristatoma, kaip šie amžiaus vidurio modernistiniai principai, perleisti per ideologijos prizmę, Lietuvoje įgavo itin skaudžias socialines pasekmes – masinį individualių gyventojų sodybų naikinimą ir gyventojų kėlimą į naujai kuriamas gyvenvietes. Kultūros namai tekste pateikiami kaip šios politinių ir ekonominių tikslų vedinos kaimo modernizacijos reprezentacinis veidas. Straipsnyje taip pat iškeliama mintis, kad kaimo modernizaciją lydėję objektai yra įdomus ir svarbus lietuviškojo XX a. architektūros palikimo fragmentas, puikiai atspindintis tarptautinių idėjų ir sovietinės ideologijos jungtį lokalioje Lietuvos provincijos terpėje. Reikšminiai žodžiai: kultūros namai, rajoninis planavimas, kultūrinio ir buitinio aptarnavimo sistema, socialistinis modernizmas, paveldas.